Pythagorean Fuzzy (R,S)-Norm Information Measure for Multicriteria Decision-Making Problem - Abhishek Guleria; Rakesh Kumar Bajaj (Advances in Fuzzy Systems)
In the present communication, a parametric (R, S)-norm information measure for the Pythagorean fuzzy set has been proposed with the proof of its validity. The monotonic behavior and maximality feature of the proposed information measure have been studied and presented. Further, an algorithm for solving the multicriteria decision-making problem with the help of the proposed information measure has been provided keeping in view of the different cases for weight criteria, when weights are unknown and other when weights are partially known. Numerical examples for each of the case have been successfully illustrated. Finally, the work has been concluded by providing the scope for future work.